Legal Protection Of Creditors In Credit Agreements With Guarantee Of Land Rights - Apip Nur (IHSA Institute, 2022)
Material guarantees have the most important and strategic position in bank lending. The collateral material that is most requested by banks is in the form of land because economically the land has favorable prospects. With the enactment of the 1996 Mortgage Law, mortgages regulated by the Civil Code and creditverbands were previously used to bind land as collateral for debts. Law Number 4 of 1996 concerning mortgage rights over land and objects related to land has provided legal protection to creditors, it is explained that agreements that create debt-receivable relationships that are guaranteed to be paid off can be made in 2 (two) forms, namely either in the form of a private deed or an authentic deed, depending on the legal provisions governing the material of the agreement